2019
DOI: 10.1111/echo.14258
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial strain and distensibility in relation to left ventricular dysfunction and prognosis in aortic stenosis

Abstract: Objective To test the relationship between left atrial (LA) distensibility (LAD), LA strain (LAS), and left ventricular (LV) dysfunction and prognosis in aortic stenosis (AS). Methods Transthoracic Doppler echocardiography was performed prospectively in 102 consecutive patients with AS (77 with severe, 25 with moderate, mean age 77 years). LA volume was calculated by the area‐length method in apical four‐ and two‐chamber views, immediately before mitral valve opening (Volmax) and at mitral valve closure (Volmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Non-invasive imaging modalities have assessed LA deformation for initial diagnosis [ 25 , 44 47 ], prognostic assessment [ 48 51 ], and evaluation of treatment response across different disease states [ 52 55 ]. Cardiac deformation analysis using strain and strain rate (SR) imaging allows early detection of pre-clinical cardiac disease.…”
Section: La Functional Assessment Techniquesmentioning
confidence: 99%
“…Non-invasive imaging modalities have assessed LA deformation for initial diagnosis [ 25 , 44 47 ], prognostic assessment [ 48 51 ], and evaluation of treatment response across different disease states [ 52 55 ]. Cardiac deformation analysis using strain and strain rate (SR) imaging allows early detection of pre-clinical cardiac disease.…”
Section: La Functional Assessment Techniquesmentioning
confidence: 99%
“…Additionally, the mean age of our patients was younger than the patient cohorts in the similar studies, which enrolled mainly AS patients with degenerative aetiology. 8 , 10 , 16 A younger patient cohort with different pathophysiology (congenital vs. degenerative) and less severe disease most probably resulted in similar LA volumes.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previous studies have shown that LA functional impairment might be present even when no structural changes are observed and might be an earlier indicator of cardiac damage in patients with AS. 8 , 9 As a result, an assessment of LA functions in asymptomatic patients might be more sensitive in predicting outcomes in CAS patients compared with an assessment of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since LA functional impairment appears to occur earlier than LA dilatation in AS, PALS could be used to identify early damage also in this setting. In fact, PALS showed to be correlated with prognosis in patients with several degrees of AS (50,51), and with the development of post-operative AF caused by fibrosis, increased myocardial stiffness, and altered relaxation ( 52), also regardless of pre-existing LA dilatation (53). Also, LA strain was the major determinant of PH in patients with severe AS and preserved LVEF (54) and a marker of LA remodeling after transcatheter aortic valve replacement (55), suggesting that a serial evaluation of LA function in these patients could help providing early surgical treatment also in AS before the development of PH and irreversible LA damage.…”
Section: Valvular Heart Diseasementioning
confidence: 93%